Management of farm chemical in compliance with standard safety policy - a survey at Ladang Zamrud, Johor / Nazren Samri - Samri, Nazren (Faculty of Plantation and Agrotechnology, 2018)
This study was conducted to determine the factors of management of farm chemical in compliance with standard safety policy. Farm chemical is one of the basis in Department of Occupational Safety And Health Malaysia. It is a principle used in workplace to manage safety and health Farm chemical is a compound word which is made up of any synthetic substances that be used in field that recognizing of things which may cause injury or harm to a person. Farm chemical such as pesticide, herbicide and fungicide is something that we as general worker or individuals using it on a day-to-day basis when applying at field. People are constantly using farm chemical without aware or knowledge on risk bear for the long term effect even the early sign of symptoms was shown. Headache, skin burns, itching and annual week absence responsible chemical worker are all imply after an acceptance farm chemical conducted. The objective of this study is to determine the compliance level of standard safety policy toward management of farm chemical. Which is the most factor influence compliance among knowledge, awareness and practices. This study was carried out at Ladang Zamrud, Kluang,Johor under PIJ Plantation and the respondent is among dependent general worker. The population in this area is 180 persons but only 85 worker focusing in task related farm chemical and the sample number is 70 person based on Krejrie and Morgan scale. The data of this study is gaining from the questionnaire that will distribute to the respondent. The data will be analysed by using reliability test and Statistical package for social science (SPSS). From the analysis, the researcher determine that awareness and practices of the factor have strong and significant relationship and awareness become the most influenced factor (p=0.000, ß=0.691) toward compliance with standard safety policy. Practices is accepted by general workers because this activity is important directly to activity their done daily and felt it. For other factor, lack of knowledge and lack of fund is become the reason why general worker low compliance with safety policy. From this study, the researcher can conclude that awareness and practices of the factor of management of farm chemical in compliance with standard safety policy have strong significant correlation relationship because all of the factor have p<0.05 and have higher Beta value. Lastly as a recommendation of this study is based on the result and also the problem that occurred when carried out this study, there are a many workers especially foreigner worker that do not understand or do not get enough knowledge about the management of farm chemical in compliance with standard safety policy. So they need to be educate with knowledge because foreigner worker major general worker in plantation. Moreover, adding other factor that can impact the result.